O processo de alfabetização de refugiados sírios: proposta de material didático para o ensino de português como língua de acolhimento - Moro, Daniela (2019)
The emergence of new waves of migration in recent years has influenced the increase in the number of immigrants and refugees in Brazil. It seems that the linguistic factor directly interferes in their lives: first, by the lack of knowledge they have of the language spoken in the country; second, for all the (inter)cultural questions that this unknown language unsettles. The immigrants bring new demands for the teaching of the Portuguese language to foreigners, such as the emerging context of alphabetization. In this context, we aim to elaborate a proposal of alphabetization material for Syrian refugees learning Portuguese and to analyze its implementation. In order to do that, we observe the extent to which the concepts of interculturality and genre of discourse were mobilized in the production of the didactic material and analyze some tasks produced to contrast them with the activities carried out by the students. From the analysis of the data, it was possible to identify that for the teaching of Portuguese as host language it is fundamental that the concepts of interculturality and genre of discourse be contemplated in the moments of production and implementation of the materials. In addition to the implementation of the didactic material, the activities carried out by the students were not always what the task proposed, but, sometimes, the communicative purpose was brought by the students themselves, as an opportunity to rework the tasks in loco.